Brian Blackford: capstone - Blackford, Brian, artist (Colorado State University. Libraries, 2013)
The artist's statement: Foremost, I believe that every work of art needs an element of enjoyment. Every task assigned, even the miserable ones, can be empowered through self-enrichment. I like to think that if I am not having fun with a work-in-progress, then I'm doing something wrong. It's a lot like that adage by art critic, John Ruskin: "When love and skill work together, expect a masterpiece." My love for clever design and thoughtful compositions are the propulsion behind my skills as an artist. In the beginning of my graphic design career, I was very much interested in learning how to use technology to create graphic solutions. Colorado State University became my choice for studying the profession because of its extensive computer and teaching resources in graphic design. However, as I began to develop as a graphic artist, I learned that my other sets of skills: drawing, painting, and sculpture; could all be applied to my graphic design work. After graduation, I plan pursuing a career in illustration through print publishing.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.